علوم القرآن کی روشنی میں رسم القرآن کا علمی وتحقیقی جائزہ: A Scholarly and Analytical Study of Rasm al-Quran in the Light of Uloom al-Quran - Aainy Syed; Mahboob Ur Rahman (Al Manhal Research Journal, 2024)
Allah Almighty has granted numerous blessings to humanity, but the Quran is the greatest of them all. The Quran is the fountainhead of guidance, which not only explains the stages of human creation but also clarifies the purpose of life, the means to attain the necessary abilities for fulfilling that purpose and provides a practical plan for striving along this path. Scholars of Islam have deeply reflected on the Quran and derived religious principles and guidelines from this book of guidance, presenting them in an accessible manner to the public. This has made it easier for the Muslim Ummah to seek Allah's knowledge and strive for His pleasure. Scholars have extracted over 80 disciplines from the Quran. ‘Uloom al-Quran’ refers to all the sciences and fields of knowledge that assist in understanding the Quran and make its comprehension easier. The foundation of these sciences was laid during the Prophet’s era, but they were systematically compiled later. Shah Waliullah Muhaddith Dehlavi divided these Quranic sciences into five branches. Among them, detailed discussion is being presented on one branch, "Rasm al-Quran" (Orthography of the Quran). From the study of ‘Uloom al-Quran’, one gains insight into the interpretation of the Quran, the wisdom behind its commands, their necessity, and significance. It helps understand the context and reasons for the revelation of specific commandments and how they can be implemented in the contemporary era. It also clarifies which rulings are Nasikh (abrogating) and which are Mansukh (abrogated), along with the reasons for abrogation. Considering the importance of understanding Islamic Shariah, learning the sciences of the Quran is essential in today’s Islamic society, which is affected by discord and strife. This is crucial to defend Islam against those who distort Quranic rulings with the intent of spreading mischief in the religion.